A 7-year old female with arthrogryposis multiplex congenita, Duane retraction syndrome, and Marcus Gunn phenomenon due to a ZC4H2 gene mutation: a clinical presentation of the Wieacker-Wolff syndrome. (3rd September 2021) - Godfrey, Deena; Torres, Alcy; Heidary, Gena; Zahoor, Hovra; Lee, Arthur; Berry, Gerard; Engle, Elizabeth
ABSTRACT: Background : Duane retraction syndrome and arthrogryposis multiplex congenita have an incidence of approximately 1:1500–1:3000 live births. However, the association of these two entities with a Marcus-Gunn might be a rare and, until now, under-recognized clinical presentation of the Wieacker-Wolff Syndrome. Patient and methods : We report a 7-year-old female with dysmorphic features, global developmental delay, arthrogryposis multiplex congenita (AMC), Duane retraction syndrome (DRS), and unilateral Marcus Gunn jaw winking. Results : Whole Exome Sequencing showed a de novo premature stop codon in ZC4H2. Extensive genetic and metabolic work was negative otherwise and Brain MRI showed delayed non-specific myelination abnormalities. She continues to have significant delays but does not have regression, seizures or other neurological complications. She has required a multidisciplinary approach for the management of her multiple contractures. Conclusion : This case confirms ZC4H2 as a cause of syndromic DRS and extends the ZC4H2 phenotype to include Marcus Gunn jaw winking.